PARADIGMATIC CHANGES IN THE PRONOMINAL SYSTEM: A SOCIOLINGUISTIC ANALYSIS OF THE THIRD PERSON PLURAL IN CAXIAS - Miranda, Antônio Luiz Alencar; Rodrigues, Rayane de Andrade; Miranda, Shirlane Maria Batista da Silva (Seven Editora, 2025)
The completion of the pronominal subject is a recurring phenomenon in Brazilian Portuguese (BP), especially in structures that employ the third-person plural. The alternation between the completed subject (they/them/the personal) and the null subject (Ø) constitutes a syntactic variable that has attracted the attention of several language scholars due to reflective processes of change and variation in BP grammar. This article, based on Variationist Sociolinguistics, investigates the completion of the pronominal subject in the third-person plural in the speech of the Caxias community, located in the interior of Maranhão. The main objective is to describe the linguistic and social factors that condition the realization of the completed forms (they/them/the personal) as opposed to the null subject (Ø). To this end, interviews with 72 informants, stratified by sex, age group, and education, were tested based on the parameters of Variation Theory. Quantitative data analysis was performed using the GoldVarb X program. The results demonstrate that the subject's completion occurs with a frequency of 61.2%, favored primarily by the presence of elements between subject and verb, gerund verb tense, disyllabic verbs, interrogative sentences, and a higher level of elementary education. The study reinforces the hypothesis of an ongoing change in Brazilian Portuguese, in which the third-person plural tends to be completed.DOI: https://doi.org/10.56238/sevened2025.038-010